2016
DOI: 10.1155/2016/3257846
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with ICU Admission following Blunt Chest Trauma

Abstract: Background. Blunt chest wall trauma accounts for over 10% of all trauma patients presenting to emergency departments worldwide. When the injury is not as severe, deciding which blunt chest wall trauma patients require a higher level of clinical input can be difficult. We hypothesized that patient factors, injury patterns, analgesia, postural condition, and positive airway pressure influence outcomes. Methods. The study population consisted of patients hospitalized with at least 3 rib fractures (RF) and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…The median age of the patients included in this study was 43 (min-max 18-87) years, which was consistent with the literature, and the majority of the patients were male. [14][15][16][17][18][19][20] Previous reports have shown that mortality rates in patients with thoracic trauma are markedly high (up to 30%). [21] Emircan et al [22] reported a 22% mortality rate among patients presenting to the emergency department with thoracic trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of the patients included in this study was 43 (min-max 18-87) years, which was consistent with the literature, and the majority of the patients were male. [14][15][16][17][18][19][20] Previous reports have shown that mortality rates in patients with thoracic trauma are markedly high (up to 30%). [21] Emircan et al [22] reported a 22% mortality rate among patients presenting to the emergency department with thoracic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[29] TRISS combines both anatomical and physiological aspects, and has been proven to be a good predictor of survival in patients with trauma. In a study that retrospectively evaluated 140 patients with thoracic trauma, Bellone et al [16] reported that only 10 of those 140 patients (7.1%) were admitted to the ICU due to clinical and radiological deterioration. In univariate and multivariate analyses, the authors of that study found that increasing orthopnea and trauma scores could be used to predict intensive care requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Traumapatient, der in eine Notaufnahme eingewiesen wurde, ein stumpfes Thoraxtrauma erlitten. In der Literatur wird eine Mortalität zwischen 4 und 20 % für diese Patienten angegeben [10].…”
Section: Das Stumpfe Thoraxtraumaunclassified
“…Blunt chest trauma accounts for around 15% of all Emergency Department (ED) trauma presentations worldwide with significant morbidity and mortality [1][2][3][4]. Currently, no evidence-based guidelines exist to assist in the management of this patient group unless the patient has severe, immediate life-threatening injuries [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no evidence-based guidelines exist to assist in the management of this patient group unless the patient has severe, immediate life-threatening injuries [1,[4][5][6]. Decisions around the ongoing management of non-life-threatening blunt chest wall trauma patients in the ED is difficult due to the frequent onset of delayed respiratory complications and clinical symptoms in the ED are not considered an accurate predictor of outcome [1,2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%